2021
DOI: 10.3389/fpsyg.2021.744432
|View full text |Cite
|
Sign up to set email alerts
|

From Whence Cometh My Help? Psychological Distress and Help-Seeking in the Evangelical Christian Church

Abstract: Seeking professional help for psychological distress is generally associated with improved outcomes and lower levels of distress. Given the saliency of religious teachings, it has been shown that aspects of Christian belief may influence adherents’ attitudes towards mental health help-seeking. Based on existing research on American Evangelicals, it was hypothesised that religious social support would positively predict attitudes towards mental health help-seeking, whilst fundamentalism, mental distress, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 61 publications
0
12
0
1
Order By: Relevance
“…The need to understand mental health literacy and social perceptions of mental health is especially prominent in evangelical communities, whose theological praxis often situates mental health as vertically representative of the inner soul or spiritual life (Lloyd, 2021a). Lloyd et al (2021) contend that this is owing to fundamentalist beliefs and literal interpretations of Scripture, which readily position all mental illnesses as tangible signs of demonic or other spiritual involvement. Whilst there are some variations to this definition, Bebbington (2003) defines evangelicalism as a Christian transdenominational movement emphasising spiritual change through being 'born again', the authority of the Bible, personal responsibility to proselytise, and the central importance of the death and resurrection of Jesus.…”
Section: Mental Illness In the Evangelical Christian Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…The need to understand mental health literacy and social perceptions of mental health is especially prominent in evangelical communities, whose theological praxis often situates mental health as vertically representative of the inner soul or spiritual life (Lloyd, 2021a). Lloyd et al (2021) contend that this is owing to fundamentalist beliefs and literal interpretations of Scripture, which readily position all mental illnesses as tangible signs of demonic or other spiritual involvement. Whilst there are some variations to this definition, Bebbington (2003) defines evangelicalism as a Christian transdenominational movement emphasising spiritual change through being 'born again', the authority of the Bible, personal responsibility to proselytise, and the central importance of the death and resurrection of Jesus.…”
Section: Mental Illness In the Evangelical Christian Contextmentioning
confidence: 99%
“…The result of accounts that portray mental illness as being caused by demonic forces and personal sin in religious settings has clearly been identified as a negative strategy for understanding and treating mental illness. Specifically, the belief that mental illness is caused by malicious, sentient beings is not only associated with greater levels of stigma within religious communities (Nearchou et al, 2018) and delayed help-seeking (Lloyd et al, 2021) but may also, according to Nie and Olson (2016), result in feelings of insecurity and unsafety, which may act to exacerbate mental health side effects. The stories illustrated a similar trend by describing instances of exorcism and forced prayer as increasing feelings of public and private shame, robbing individuals of their agency and ultimately blocking recovery from mental health difficulties.…”
Section: The Negative Consequences Of a Spiritualised Aetiologymentioning
confidence: 99%
“…Indeed, there is some evidence to suggest that involvement in religious life may provide an important social setting for adherents to develop coping strategies and worldviews, which lend themselves to better mental wellbeing ( Hayward and Krause, 2014 ; Kinghorn, 2016 ). Taken together, religious engagement seems to be broadly associated with enhanced wellbeing outcomes, which may be partly explained by the inherently social nature of belonging to a religious group ( Lloyd et al, 2021 ). In addition to the socially-derived wellbeing benefits, research has also shown that religious cognition is related to health outcomes ( Page et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…With over 600 million global followers in which over 2 million are in the United Kingdom ( Pew Research Centre, 2015 ; Evangelical Alliance, 2020 ), evangelicalism can be thought of as a Protestant transdenominational movement, which places an emphasis on the literal interpretation of biblical texts; the need for a personal saving relationship with Jesus Christ; and the expectation of spiritual health and wellbeing for believers ( Bebbington, 1989 ; Stackhouse, 2007 ). Considering their global prominence and potentially spiritualised conceptualisation of mental illness ( Lloyd and Kotera, 2021 ; Lloyd et al, 2021 ), there is clear need to better understand the Evangelical worldview and how this relates to perceptions of mental health and help-seeking behaviours.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation